Theoretical and legal aspects of interaction between national and supranational legal systems in globalization: towards problem statement - Саннікова, М. В. (Theory and practice of jurisprudence, 2016)
This paper is devoted to the theoretical and legal aspects of the interaction of legal Ukraine supranational jurisdictions. The main attention is paid to areas such as interaction, determines the factors that caused it. The changes in the legal system, the system of sources of law and forms of external expression.